2018
DOI: 10.1111/cas.13657
|View full text |Cite
|
Sign up to set email alerts
|

HuR stabilizes TFAM mRNA in an ATM/p38‐dependent manner in ionizing irradiated cancer cells

Abstract: Mitochondrial transcription factor A (TFAM) plays key roles in transcription and maintenance of mtDNA. It has been reported that TFAM could promote the proliferation and tumorigenesis of cells under stressed conditions. Previous evidence showed ionizing radiation stimulated the expression of TFAM, the replication of mtDNA, and the activity of mtDNA‐encoded cytochrome C oxidase. However, little is known about the mechanism of TFAM regulation in irradiated cells. In this article, we explored the role of mRNA sta… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
21
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 24 publications
(22 citation statements)
references
References 42 publications
1
21
0
Order By: Relevance
“…TFAM is a regulator of mitochondrial biogenesis and plays an important role in the maintenance of mitochondrial DNA integrity and mitochondrial functions. It has been reported that inhibition of TFAM led to increased sensitivity of cancer cells to cisplatin, doxorubicin, or ionizing irradiation [26,27]. Mitochondrial dysfunctions could result in variations of autophagy.…”
Section: Discussionmentioning
confidence: 99%
“…TFAM is a regulator of mitochondrial biogenesis and plays an important role in the maintenance of mitochondrial DNA integrity and mitochondrial functions. It has been reported that inhibition of TFAM led to increased sensitivity of cancer cells to cisplatin, doxorubicin, or ionizing irradiation [26,27]. Mitochondrial dysfunctions could result in variations of autophagy.…”
Section: Discussionmentioning
confidence: 99%
“…Total DNA was extracted from the parental XTC.UC1, XTC.UC1/MIEAP, and XTC.UC1/PARK2 cells using DNeasy Blood & Tissue Kit (Qiagen). Quantitative PCR according to the ΔΔCt method was carried out as described previously 27,28 . 12S rDNA encoded by mtDNA and β‐actin encoded by nDNA were quantified, and the mtDNA / nDNA ratio was used to estimate the relative mtDNA copy number, ie the relative amounts of mitochondria.…”
Section: Methodsmentioning
confidence: 99%
“…In addition, the TFAM mRNA is subject to complex post-transcriptional regulation ( Figure 4 ), including stabilization by RNA-binding proteins [ 226 ] and various microRNAs [ 227 , 228 , 229 , 230 ]. For example, microRNA-494 (mir494) was shown to downregulate TFAM expression in proliferating myoblasts by binding to 3′-UTR within the mRNA sequence.…”
Section: Regulation Of Mthmg Proteinsmentioning
confidence: 99%